2020
DOI: 10.1186/s12960-020-00466-y
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean nurse migration—a scoping review

Abstract: Background: The migration of Caribbean nurses, particularly to developed countries such as Canada, the United States, and the United Kingdom, remains a matter of concern for most countries of the region. With nursing vacancy rates averaging 40%, individual countries and the region collectively are challenged to address this issue through the development and implementation of sustainable, feasible strategies. The aim of this scoping review is to examine the amount, type, sources, distribution, and focus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Several papers, notably reviews, provide an evidence-based underpinning for the third area of action: to strengthen nurse leadership to ensure that nurses have an influential role in health policy formulation and decision-making, and contribute to the effectiveness of health and social care systems. These include a scoping review to develop metrics for nursing quality of care for low- and middle-income countries, in order to better demonstrate impact [ 13 ], a report on the introduction and extension of nurse prescribing of medicines in 13 European countries, which highlights policy engagement to support advanced practice [ 14 ], and a scoping review of the policy implications, positive and negative, of Caribbean nurse migration [ 15 ], and a review highlighting the use of advanced practice nurses as a strategy to enable more equitable access to health care in the countries of the Western Pacific Region [ 16 ].…”
mentioning
confidence: 99%
“…Several papers, notably reviews, provide an evidence-based underpinning for the third area of action: to strengthen nurse leadership to ensure that nurses have an influential role in health policy formulation and decision-making, and contribute to the effectiveness of health and social care systems. These include a scoping review to develop metrics for nursing quality of care for low- and middle-income countries, in order to better demonstrate impact [ 13 ], a report on the introduction and extension of nurse prescribing of medicines in 13 European countries, which highlights policy engagement to support advanced practice [ 14 ], and a scoping review of the policy implications, positive and negative, of Caribbean nurse migration [ 15 ], and a review highlighting the use of advanced practice nurses as a strategy to enable more equitable access to health care in the countries of the Western Pacific Region [ 16 ].…”
mentioning
confidence: 99%
“…Severe nursing shortages in developing countries, compounded by aging populations, increased health service specialization, and technological complexity are major contributors to nurse migration [ 22 ]. In the Caribbean, nurses migrate for many reasons including better remuneration, improved work conditions, and career advancement [ 23 , 24 ]. Historically, nurse migration has resulted in an imbalance of the skilled nursing workforce favoring wealthier countries; a phenomenon expected to continue in Jamaica and the wider Caribbean without significant intervention [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Caribbean Community and Common Market (CARICOM) is a group of 20 developing countries in the Caribbean that have united to improve standards of living and work and to enhance levels of international competitiveness [ 25 ]. A scoping review by Rolle Sands et al, which was published after our search was completed, examined the conceptual and empirical literature pertaining to nurse out-migration from the CARICOM region [ 24 ]. Their findings supported a need for future research on the impact of nurse migration on health systems and population health within Caribbean countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is exacerbated by the observation that while nurses represent more than 50% of the workforce, their voices are diluted or unheard within the context of leadership within health systems (Sigma Theta Tau International, 2017). It is possible that the external migration challenges result in more experienced nurses leaving the Caribbean region (Commonwealth Secretariat, 2015;Rolle Sands, Ingraham, & Salami, 2020), thereby requiring younger nurses to assume positions of leadership. A number of factors have been identified that facilitate external migration from the Caribbean region including professional and socioeconomic (Commonwealth Secretariat, 2015;Rolle Sands et al, 2020;Salmon, Yan, Hewitt, & Guisinger, 2007;Trines, 2018).…”
mentioning
confidence: 99%
“…It is possible that the external migration challenges result in more experienced nurses leaving the Caribbean region (Commonwealth Secretariat, 2015;Rolle Sands, Ingraham, & Salami, 2020), thereby requiring younger nurses to assume positions of leadership. A number of factors have been identified that facilitate external migration from the Caribbean region including professional and socioeconomic (Commonwealth Secretariat, 2015;Rolle Sands et al, 2020;Salmon, Yan, Hewitt, & Guisinger, 2007;Trines, 2018). This research project explored perspectives of nurses functioning at the junior to middle level of management about their readiness to transition into positions of leadership within the health sector.…”
mentioning
confidence: 99%